Optimal design of helical flute of irregular tooth end milling cutter based on particle swarm optimization algorithm. (April 2022) - Yu, Haibin; Zheng, Minli; Zhang, Wei; Nie, Wanying; Bian, Tianchen
Due to the variable pitch angle and helix angle of the irregular tooth end milling cutter, the mass of the integral end milling cutter is eccentric, and the high stability and precision design of the irregular tooth end milling cutter is still a challenge. Aiming at the influence of dynamic balance of irregular tooth end milling cutter which can not be ignored in high-speed milling, the parameterized design of radial section of irregular tooth end milling cutter was carried out. Based on the space transformation law of the centroid of helical flute, a new method for calculating the centroid coordinate of end milling cutter was put forward, and a general mathematical model of eccentricity of integral end milling cutter was given. It was proved that this model could accurately calculate the centroid position and eccentricity of the end milling cutter. The influence of pitch difference angle and helix difference angle on eccentricity of end milling cutter was studied and analyzed. The particle swarm optimization (PSO) algorithm was creatively applied to optimize the helical flute shape of the end milling cutter, the curvature radius of helical flute curve is optimized, so that the centroid coordinate is infinitely close to the origin of coordinate. The number of iterations was set to 200. In the 32nd iteration, the result approached to infinitesimal, the final function converged, and obtained the groove curvature radius of the milling cuter with the smallest eccentricity. The optimized eccentricity of the end milling cutter is infinitesimal, which can make the vibration damping performance of the end milling cutter be fully developed. On the basis of ensuring the same cutting performance, the cutting tool unbalance was effectively reduced and the dynamic performance of milling cutter was further improved.